2022
DOI: 10.3390/ijms232113045
|View full text |Cite
|
Sign up to set email alerts
|

Linking Nonalcoholic Fatty Liver Disease and Brain Disease: Focusing on Bile Acid Signaling

Abstract: A metabolic illness known as non-alcoholic fatty liver disease (NAFLD), affects more than one-quarter of the world’s population. Bile acids (BAs), as detergents involved in lipid digestion, show an abnormal metabolism in patients with NAFLD. However, BAs can affect other organs as well, such as the brain, where it has a neuroprotective effect. According to a series of studies, brain disorders may be extrahepatic manifestations of NAFLD, such as depression, changes to the cerebrovascular system, and worsening c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 224 publications
0
3
0
Order By: Relevance
“…The reason for these problems is likely multifactorial, but others have proposed that a mild hepatic encephalopathy or a 'new' composite metabolic encephalopathy might exist in metabolically dysfunctional patients with or without obesity. [31][32][33][34][35] If present, this could adversely impact QOL, particularly attention span and low activity level, which are well-known problems in HE. However, more studies are needed to explore this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for these problems is likely multifactorial, but others have proposed that a mild hepatic encephalopathy or a 'new' composite metabolic encephalopathy might exist in metabolically dysfunctional patients with or without obesity. [31][32][33][34][35] If present, this could adversely impact QOL, particularly attention span and low activity level, which are well-known problems in HE. However, more studies are needed to explore this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of each SIP statement, it is evident that physical discomfort, reduced activity levels, especially in the sphere of sexuality, and challenges related to attention are the prevailing issues that significantly impact the daily lives of our study participants—and more so in patients with MASH. The reason for these problems is likely multifactorial, but others have proposed that a mild hepatic encephalopathy or a ‘new’ composite metabolic encephalopathy might exist in metabolically dysfunctional patients with or without obesity 31–35 . If present, this could adversely impact QOL, particularly attention span and low activity level, which are well‐known problems in HE.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of these neural circuits can result in several aberrant neurological processes, including neuroinflammation, impaired cognitive abilities, seizures, and demyelination. Secondary bile acids can be discovered in the brains of people suffering from AD, and the rise in the content is positively connected to cognitive impairment and brain imaging alterations [109]. In a clinical trial, it was observed that AD patients exhibited a significant decrease in the concentration of cholic acid, which is the main bile acid (BA), compared to non-AD patients.…”
Section: Bile Acidmentioning
confidence: 99%
“…Earlier studies have also described that bile acids transmit signals to the brain through both direct or indirect pathways and participate in the development of brain diseases, thereby implying a correlation between bile acids and mental illnesses. Elevated serum bile acids have been proven to increase BBB permeability and transmit signals to the central nervous system via FXR, TGR5, etc., eventually elevating the risk of mental disorders ( 9 ).However, the underlying mechanisms by which bile acid signals affect the occurrence of anxiety behavior have not been fully elucidated ( 10 ). The article is divided into two main sections.…”
Section: Introductionmentioning
confidence: 99%